Risk management - Danilova, Anna; Vlasenko, Ludmila (My University, 2014)
In ideal risk management, a prioritization process is followed whereby the risks with the greatest loss (or impact) and the greatest probability of occurring are handled first, and risks with lower probability of occurrence and lower loss are handled in descending order. In practice the process of assessing overall risk can be difficult, and balancing resources used to mitigate between risks with a high probability of occurrence but lower loss versus a risk with high loss but lower probability of occurrence can often be mishandled. These risks can reduce the productivity of knowledge workers, decrease cost- effectiveness, profitability, service, quality, reputation, brand value, and earnings quality. Intangible risk management allows risk management to create immediate value from the identification and reduction of risks that reduce productivity.
Keywords: productivity; earnings; risk management; продуктивність; дохід; управління ризиками; производительность; заработок; управление рисками; кафедра ділової іноземної мови та міжнародної комунікації